Control interno y su relación con la gestión administrativas de la liga deportiva cantonal de Quevedo, año 2012" - Tovar Otañez, José Luís (2016)
All administrative processes applied in the institution are covered in regulations Agency Sports and League Cantonal de Quevedo located in Jaime Roldos and Twenty (Stage 7 October) avenue aims to raise awareness of the reality that occurs in this institution due to administrative management verifying compliance to regulations established by the body, using methods for gathering information to know what problems to conclude covers and efficiently and recommend solutions to correct administrative management and hoping that the hypothesis accept or reject The methodology used was the inductive, descriptive and analytical methods that contributed much to the phases of the audit, the types of research such as literature and field hypotheses were accepted that were referenced the legal framework to assess compliance of the activities executed as a result was obtained that the revolving funds of the box are not spare parts to continue with daily activities, the objectives are not well established which do not fully comply performing the audit report detailed the observations obtained in the investigation reached the conclusion LigaDeportiva Cantonal de Quevedo should choose very clear and precise objectives to be attained within stipulated period of time, have backup documentation of all activities events have greater control of the assets you have to avoid property losses generating an unnecessary expense. In conclusion of the research work it was shown not applied studies administrative management indicators with 42.86% level of risk, the replacement of worn values in the administration with a 22.23% level of risk and loss of institutional goods areas 27.28% a moderate risk level